Aktivitas Belajar Mahasiswa dalam Perkuliahan Pendidikan IPS dengan Menerapkan Model Pembelajran Kooperatif Tipe Make A Match - Rusmawan Rusmawan; Puji Purnomo (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2021)
The low level of student activity in Social Studies Education courses is a problem for students' ability to interact well with fellow students, lecturers and learning resources. This condition requires the application of an effective learning model to increase student learning activity in the classroom. This study answered two research questions, namely how student learning activities in Social Studies Education courses use Make a Match cooperative learning and how to apply Make a Match cooperative learning models in increasing student learning activities in Social Studies Education for Elementary School courses. This research is a Classroom Action Research (CAR). The subjects of this study were the fifth semester students of Class C of the Elementary School Teacher Education Study Program who attended the Social Studies Education for Elementary School course as many as 47 students. Research data were collected through observation. The data analysis technique used was descriptive analysis. The results showed that (1) the dominant aspects of learning activities in Social Studies Education courses with the Make a Match type cooperative learning model were aspects of group interaction and aspects of answering questions; and (2) Social Studies Education for Elementary School courses with the Make a Match type cooperative learning model can increase student learning activities, the indications are that the percentage score of student learning activities is above 70 (78.72%).